2020
DOI: 10.1111/jpm.12679
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting suicidal ideation among premenopausal and postmenopausal women

Abstract: Accessible summary What is known on the subject? Pre‐ and postmenopausal women (PPW) experience changes in physical, psychological and social health. South‐East Asia’s female suicide rate is the highest compared with other countries, and the suicide rate of PPW in these countries continues to increase. The most influential factor in Asian women’s suicidal ideation is family conflict; specifically, if PPW in South Korea cannot express their anger, it results in a culture‐bound syndrome called “Hwa‐Byung.” How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…In our review, the most common risk factor associated with suicide and/or suicidal behaviour due to domestic violence was mental illness and/or psychological distress [27,29,30,33]. Domestic violence has significant health consequences for women, children, and families.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In our review, the most common risk factor associated with suicide and/or suicidal behaviour due to domestic violence was mental illness and/or psychological distress [27,29,30,33]. Domestic violence has significant health consequences for women, children, and families.…”
Section: Discussionmentioning
confidence: 94%
“…The 19 articles included in the review were peer reviewed and original. Sixteen of the articles were conducted in Southeast Asia; four were from India [17][18][19][20]; two each from Bangladesh [21,22], Afghanistan [23,24], and China [25,26]; and one each from Sri Lanka [27], Nepal [8], Iran [28], South Korea [29], and the Philippines [30]. One study each from South-Asian immigrants in the UK [31] and multiple countries in Southeast Asia [32] and a study from several countries, which included South America, Asia, Africa, Oceania, and Europe, were included [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women have more access to prescription medications than men and men have more access to guns, which means that suicidal men use more lethal means—women may thus attempt suicide more often, but men more often complete suicide [ 59 ]. Furthermore, women are more likely than men to report suicidal ideation and to, thus, receive protective social support [ 60 , 61 ]. However, age at menopause was positively associated with the intensity of suicidal ideation in sample of 25 women with DD [ 40 ], which suggests that neuroprotection conferred by estrogens may play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Insomnia is a representative physical symptom that appears in the early stages of Hwabyung, and sleep time and quality are related to Hwabyung symptoms [ 21 , 22 , 23 ]. The Hwabyung experienced by middle-aged women before and after menopause is a symptom that should be treated seriously because it can affect extreme thoughts, such as suicide [ 24 ]. When looking at the results of previous studies that showed that decreased sleep time increased suicidal ideation [ 25 , 26 , 27 ], it is evident that a continuous decrease in sleep time can hinder healthy daily life factors.…”
Section: Introductionmentioning
confidence: 99%